Image-guided bone marrow aspirate concentrate and platelet-rich plasma therapy for a chronic high-grade anterior cruciate ligament tear: a case report - Venkatesh Movva; Anand Alluru; Syed Khaleel; Sunitha Manne Mudhu; Vijayalakshmi Venkatesan (International Journal of Research in Medical Sciences, 2026)
The anterior cruciate ligament (ACL) is a critical stabilizing structure of the knee joint, responsible for maintaining both anteroposterior and rotational stability. ACL injuries are among the most common sports-related ligamentous injuries to cause debilitating condition. Surgical reconstruction forms the end point of recommendation, nevertheless emerging techniques like orthobiologics using bone marrow aspirate concentrate (BMAC) and platelet-rich plasma (PRP) form alternate therapy. A 26-year-old male cyclist and fitness enthusiast presented with chronic knee instability and functional limitation secondary to a high-grade ACL tear. The patient continued to experience recurrent episodes of instability and was advised to undergo ACL reconstruction. Reluctant to pursue surgical intervention, the patient opted to undergo image-guided orthobiologic treatment. BMAC and high-concentration PRP were administered under ultrasound and fluoroscopic guidance directly into the injured ACL fibers, infrapatellar region, and intra-articular compartment. The procedure was performed on an outpatient basis. Clinical follow-up demonstrated progressive functional improvement over six months. Resting pain resolved within the first month, while objective clinical examination revealed improvement in ligament stability as reflected by Lachman test (Grade II to Grade I) with a firm endpoint. At six months, the patient reported approximately 90% functional recovery, complete resolution of subjective instability episodes, and successful return to long-distance cycling, aerobic exercise, and agility-based activities without pain or stiffness which was noteworthy. The observed clinical and functional improvements suggest that targeted regenerative intervention(s) offer feasible line of treatment in the management of ACL tear where conventional conservative management has failed.